Factors determining and resulting in the suspension of elective surgical procedures: Integrative review (Research, Society and Development, 2024)
Objective: to identify the main causes and consequences of the suspension of elective surgical procedures. Methods: this is an integrative review that followed recommendations adapted from the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. From the Virtual Health Library Portal, the bases of Latin American and Caribbean Literature in Health Sciences and the Nursing Database were chosen, with the Boolean operators: “cancellation”, “suspension”, “surgery” – between 2013 and 2023. Results: two main thematic categories stood out – a) causes of suspension of elective surgeries, obtaining two subcategories: intrinsic factors and extrinsic factors for the surgical patient; and b) repercussions of the suspension of elective surgeries. Conclusion: the main reasons for suspending surgeries were the patient's clinical causes, lack of beds and material resources. As consequences, there was a psychological shock to the patient and their families and an increase in hospital expenses. It is important to establish interventions during the planning phase of the surgical procedure, in order to mitigate the outcomes generated by these suspensions.